Analyzing the performance of E- government in Jordan in the period 2008 – 2016 - Ismail Ghazi Shayeb, Naseem Masoud Asad (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2018)
E-government means the use of information and communication technologies to promote and streamline the activities of public organizations. The past ten years have witnessed a tremendous development in the field of communications and information technology, which has made the presence of e-government an urgent necessity to increase government efficiency and effectiveness. In the last decade the government of Jordan has invested heavily in E-government projects to deliver efficient services to populations. However the global rank of E-government of Jordan is still in low rank according to the global countries. The purpose of our research is to study and analyze the factors affecting the development and progress of e-government in Jordan from 2008 to 2016. In this research we gathered our data about E-government of Jordan from the United Nations e-government surveys. The research shows that despite the development of infrastructure in the field of communications and information technology, the weakness of electronic services provided, and the lack of funds to build integrated electronic governments is what led to the weakness and decline of e-government performance in Jordan. The provision of more electronic services and the improvement of the quality of these services in addition to providing the necessary capital will play an indispensable role in improving the performance of e-government in Jordan and thus get a high ranking compared to global countries. This study allows e-government officials to know the reasons for the decline in the performance of e-government despite the efforts made. Thus developing radical solutions to these problems if possible.
Keywords: E-government, Jordan, Obstacles, ICT